Adverse childhood experiences amplify the longitudinal associations of adult daily stress and health. (December 2021) - Kong, Jooyoung; Liu, Yin; Goldberg, Jaime; Almeida, David M.
Abstract: Background and objective: The long-term negative impact of Adverse Childhood Experiences (ACEs) is now well-recognized; however, little research has explored the link between ACEs and daily stress processes in adulthood. The current study aimed to examine the effect of ACEs in the association between daily stressor exposure and daily negative affect, and whether such associations would predict long-term health and well-being. Methods: Using data from the National Study of Daily Experiences 2 (NSDE 2) and the Midlife in the United States (MIDUS) studies, multilevel moderated mediation analyses were conducted to account for daily measurements nested within individuals. We tested whether the indirect effect of daily stressor exposure on prospective chronic health conditions and prospective depressive symptoms through daily negative affect would differ by adults' levels of ACEs. Results: We found significant positive associations between daily stressor exposure and daily negative affect at both the within- and between-person levels. Between-person daily negative affect was, in turn, associated with more chronic health conditions and higher depressive symptoms ten years later. This indirect effect was stronger for adults with high ACEs compared to those with low ACEs. Conclusions: The current study demonstrated that a history of ACEs may exacerbate the negative health effects of daily stress processes over time. Programs focusing on coping with daily stressors and resilience may benefit adults with ACEs and promote their health and well-being.